Peran Olahraga Mini Soccer Dalam Meningkatkan Kesehatan Fisik Dan Sosial Masyarakat Nagari Sungai Durian - Windi Lestari; Nasywa .; Shatzi Laura Fetris; Ryandra Sastra; Rayhan Azky Desva; Yulianti Rasyid (CV. ITTC INDONESIA, 2025)
Mini soccer is a variation of soccer with fewer players and a smaller field, so it prioritizes speed and teamwork. The mini soccer activity held at Nagari Sungai Durian from 8 to 11 February 2025 is one of the 2025 UNP Sungai Durian Real Work Lecture (KKN) work programs. This research aims to analyze the role of mini soccer in improving the physical health and social interaction of the community. Data was collected through participatory observation during activities and field documentation. The research results show that mini soccer is able to improve players' physical fitness through intense physical activity, as well as strengthening social relations between residents. Competitive matches and high enthusiasm from the audience show that mini soccer plays an important role in maintaining physical health as well as strengthening the social solidarity of the Nagari Sungai Durian community.